Vanaf laat-strukturalisme na post- strukturalisme: "n Kontekstualisering van Jean-François Lyotard se Discours, Figure - Beukes, Johann (HTS teologiese studies, 2002)
From late-structuralism to post-structuralism: A contextualization of Jean-François Lyotard’s Discours, FigureIn this article the post-structuralist legacy of French philosopher Jean-François Lyotard (1924-1998) is being surveyed with specific regard to his first major publication, Discours, Figure (1971). The initial impact of this text on the post-structuralist debate is being explored, as well as the way in which it brought Lyotard in direct confrontation with Jacques Derrida, the then mainstream representative of (late) structuralism, with specific regard to Lyotard’s battle against the “imperialism of the text” and his own critical departure from phenomenology.